FAT AND WATER DISTRIBUTION PATTERNS IN THE FLESH OF THE COMMON CAT - FISH WALLAGO ATTU (BL.& SCHN.) - JAFRI, A K (Fishery Technology, 2016)
The quantitative distributional pattern of fat and water has been studied in the flesh of the various zones corresponding to the dorsal and ventral regions of the body of a common cat-fish, W. attu. The ventral aspect of the body showed more accumulation of fat than the dorsal aspect, The fat content in the ventral region also exhibited an increase from the anterior to the posterior zones. In the dorsal region, however, the back portion of the body, behind the dorsal fin, generally possessed low fat content. On an average, the highest fat accumulation was observed in the caudal peduncle region. The distribution of water followed an almost opposite pattern of distribution, indicating an inverse relationship with fat.